Аудит системи економічної безпеки підприємства - Москаль, Н. В.; Moskal, N. V. (Видавництво Львівської політехніки, 2017)
Розглянуто теоретичні аспекти аудиту системи економічної безпеки підприємства, зокрема, досліджено структуру системи економічної безпеки і визначено мету, предмет, об’єкти аудиту, розроблено критерії оцінки цієї системи та завдання аудиту. Метою аудиту системи економічної безпеки підприємства є висловлення незалежного судження аудитора стосовно адекватності цієї системи та ефективності її функціонування. Предметом такого аудиту є сукупність інформації про організацію системи економічної безпеки, її структуру, завдання, методику їх виконання, процес функціонування та результати, вплив цієї системи на рівень економічної безпеки підприємства. Критерії оцінки системи економічної безпеки підприємства доцільно поділити на дві групи: адекватність (комплексність, безперервність, компетентність) та ефективність (результативність, економічна доцільність, своєчасність).

The scientific article studied the theoretical aspects of the audit of economic security of enterprise. The level of economic security is an important indicator of the financial situation, stability, prospects of the company for its owners, staff and investors. Business entities are adopting a system of economic security to determine the level of economic security, to monitor its changes and create conditions for its improvement. Audit is an independent and competent control with which business entities can to verify the adequacy and effectiveness of economic security system. Scientific article studies the structure of the system of economic security and defines the audit purpose, audit objects, the article develops the criteria for evaluation of this system and objectives of the audit. The purpose of auditing of economic security system, is to express an independent auditors judgment regarding the adequacy of this system and the efficiency of its operation. The subject of this auditing is a set of information about: the organization of economic security system, its structure, objectives, methods of implementation and results, impact of this system on the level of economic security. Objects of audit: the organizational support of the system of economic security, the functioning of this system, reports, recommendations and suggestions to enhance the level of economic security and the level of economic security for the period of the system activity. Criteria for evaluation of economic security system are divided into two groups: adequacy (comprehensiveness, continuity, competence) and performance (effectiveness, economic feasibility, timeliness). The proposed auditing objectives take into account the goal of audit, criteria for evaluation and objects of audit.
Audit of economic security system of enterprise
Keywords: економічна безпека; аудит системи економічної безпеки; предмет аудиту; об’єкти аудиту; критерії оцінки системи економічної безпеки підприємства; economic security; audit of economic security system; objects of auditing; criteria for evaluation of economic security of enterprise; 657.6